2010
DOI: 10.1111/j.1532-5415.2010.03202.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Activity of Older Adults Hospitalized with Acute Medical Illness

Abstract: OBJECTIVES To describe the amount and patterns of ambulatory activity in hospitalized older adults over consecutive hospital days. DESIGN Observational cohort study. SETTING University teaching hospital Acute Care for Elderly (ACE) unit. PARTICIPANTS Adults aged 65 and older (N = 239) who wore a step activity monitor during their hospital stay. MEASUREMENTS Total number of steps per 24-hour day. Mean daily steps were calculated based on number of days the step activity monitor was worn. RESULTS Mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
156
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(160 citation statements)
references
References 21 publications
3
156
1
Order By: Relevance
“…Profound inactivity characterizes acute hospitalization in older adults and can significantly and independently contribute to muscle and functional loss (11,12). Several studies have shown that shortterm bed rest leads to rapid deterioration of muscle mass and strength of the lower extremity even in healthy older subjects (7,24).…”
mentioning
confidence: 99%
“…Profound inactivity characterizes acute hospitalization in older adults and can significantly and independently contribute to muscle and functional loss (11,12). Several studies have shown that shortterm bed rest leads to rapid deterioration of muscle mass and strength of the lower extremity even in healthy older subjects (7,24).…”
mentioning
confidence: 99%
“…4,6 Patients with longer hospital stays have been shown to be more physically inactive during hospital stay, compared with patients with shorter lengths of stay. 7 Although bed rest and consequent inactivity associated with illness and hospitalization have significant implications for medical patients, both in hospital and after discharge and rehabilitation, recent reviews showed that early physical rehabilitation care for acute hospitalized old adults leads to functional benefits. 3,9 In general, physical activity, mobilization and resistance training seem most frequently investigated in frail old patients.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Functional decline has been strongly related to patients' age and preadmission activities of daily living status. 4,[6][7][8] This is furthermore important for the high number of readmissions in this patient group. 4,6 Patients with longer hospital stays have been shown to be more physically inactive during hospital stay, compared with patients with shorter lengths of stay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adults over 65 years of age account for 40% of all hospital admissions and are clearly at increased risk of being physically incapacitated or placed on bed rest for an extended period of time (Kozak et al 2005;Wolfe et al 2008;Fisher et al 2011). Irrespective of age, physical inactivity alone has been repeatedly shown to facilitate or accelerate the deterioration of key health outcomes, including insulin signalling, muscle mass, motor control, and functional capacity (Clark et al 2007;Paddon-Jones et al 2005;Urso et al 2006aUrso et al , 2006b).…”
Section: Effect Of Aging On Building Muscle In Response To Proteinmentioning
confidence: 99%